Les ressources humaines - Laflamme, Roch (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Les ressources humaines," edited by Dimitri Weiss.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Human resources; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z